How sapient is homo economicus? The evolutionary origins of trade, ethics and economic rationality - Kaushik Basu; Ashok Guha (Cornell University, Center for Analytical Economics (CAE), 2009)
The paper argues that economism and, in particular, the individual drive to maximize utility and amass profit are not enough to ensure the efficient functioning of an economy; and that even for elementary economic activities, such as trade, exchange and contracting to occur smoothly, it is essential that human beings be endowed with appropriate social norms, such as a critical level of trustworthiness. This, in turn, implies that an economy's development can depend significantly on whether the citizenry is endowed with the relevant norms. Where these norms come from and how they gather stability remain open questions, though we can get some important insights from theories of evolutionary processes.
Keywords: 330; Rationales Verhalten; Soziale Norm; Evolutionsökonomik; Public Choice; Theorie